Pelatihan pembuatan briket tempurung kelapa pada masyarakat petani di Kabupaten Bulukumba - Sudding Sudding (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The problem faced by the farming community in theTugondeng Village, Herlang District, Bulukumba Regencywas that they did not have the knowledge and skills to processthe coconut shell. The coconut shell is abundant in Tugondengvillage area and it can be an alternative fuel briquette, whichhas high economic value. If this potential is managed properly,it will be able to lift the economy of the local farmingcommunity. The approach taken in this program was toprovide training in the form of lectures and directdemonstrations on how to process coconut shells intobriquettes, discussions and question, and answer sessions withthe community members regarding the things needed bytrainees related to the manufacture of briquettes, includinghow to market them. The PKM output is coconut shellbriquettes that can meet the fuel needs of the local community,and can even be exported overseas.